Contradictions and paradoxes of the urban management model in the metropolitan area of Guadalajara, Jalisco, Mexico - Lara, Josefina (Pontifícia Universidade Católica de São Paulo, 2019)
In Mexico, the metropolitan phenomenon is identified as a public policy problem, which has led to the design of institutional structures and coordination mechanisms whose objective is to attempt to manage the country’s metropolitan areas and make them governable. We conducted an exploratory analysis of the urban management problems of the Guadalajara metropolitan area, where, despite the existence of new coordination levels, there has been no substantial improvement in the allocation of public resources, nor in intermunicipal cooperation or in the making of urban policies. Our aim is to reveal the contradictions and paradoxes of a model in which a normative framework of urban management and a chaotic reality coexist.